Body Language in Youtube-Based Product Endorsements by Indonesian Influencers - Winiharti, Menik; Hensen, Hensen (Humaniora: Journal of Indonesia Culture and Society, 2026)
Body language plays a crucial role in non-verbal communication by expressing emotions, attitudes, and intentions. Its dynamic nature allows individuals to convey diverse meanings, particularly in professional and business settings. Given the limited studies on the association between body language and product endorsement in the Indonesian digital context, the present research aims to fill this gap. Therefore, the goal is to identify the types of body language Indonesian influencers use in their YouTube videos. It also aims to identify their contextual meanings. The data for this research are collected from videos of three Indonesian YouTube influencers. A qualitative approach is employed to analyze body language. The findings highlight six common types of body language used by the influencers: hand gestures, facial expressions, finger gestures, eyebrow movements, body posture, and overall body movements. These non-verbal cues are strategically used to reinforce product reviews and increase viewer engagement. By incorporating these physical expressions, influencers can more effectively communicate their promotional messages and foster a deeper connection with their audience. These findings underscore the importance of body language in enhancing the persuasive power of online endorsements, particularly on social media platforms, within the Indonesian cultural context.